Safe local onion (Hanh Tam) flyer - Nguyen, N.H.; Tran, D.Q.; Nguyen, T.T.; Hoa, D.T.; Simelton, Elisabeth; Le, T.T. (World Agroforestry Centre, 2021)
Local onion (Hanh Tam) - bean rotation is considered as a climate-smart agriculture intervention to adapt to drought condition during the summer-autumn season in Can Loc district, Ha Tinh province. This poster summaries key information on scale, economic as well as environmental benefits of this practice and can be used to introduce the practice to various stakeholders, including buyers of agricultural products.